Bleeding Tendency with Platelet Dysfunction and Albinism - Murakami, M; Odake, K; Matsuda, T; Manmi, S; Takase, M; Imura, M; Toyama, T (Thrombosis and Haemostasis, 1972)
A Japanese boy, who had combined congenital defects - a hemorrhagic disorder due to abnormal platelet function and incomplete albinism, was described. His parents were first cousins. Platelet aggregation by collagen and epinephrine was markedly defective. A rapid disaggregation was observed in ADP-induced aggregation. Platelet factor 3 availability and in vitro adhesiveness were subnormal, while platelet factor 3 activity was normal. Defective ADP release was associated with impaired aggregation by collagen. Before aggregation, labeled adenine nucleotide pattern in patient’s platelets was not different from that in normal platelets. The increase of intermediates of platelet ATP breakdown, such as AMP and IMP, was less in patient’s platelets after collagen-induced aggregation. The release of labeled ATP and ADP in patient’s plasma was less than that in normal plasma.